2016
DOI: 10.1071/sh14218
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of the human papillomavirus vaccine on the incidence proportion of genital warts in French women (EFFICAE study): a multicentric prospective observational study

Abstract: A trend for a non-significant decreased incidence proportion of GW was observed in young women below 20 years who are more frequently vaccinated. This may be the result of HPV vaccination and suggests that a substantial increase in vaccine coverage could lead to a more pronounced decreased incidence proportion of GW in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Taking into account warts, it has been shown that in French women aged between 15 and 18 years, the incidence of genital warts significantly decreased in the period 2008-2012 after the introduction of the quadrivalent vaccine [8]; in Denmark, 5 years after the introduction of the same vaccine the incidence of genital warts decreased by 55% in women aged 12-35 years. Besides, in 12-29 years old men, the incidence of genital warts decreased by 37%, indicating the development of herd immunity [9].…”
Section: Hpv Epidemiology In Europe and In Italymentioning
confidence: 99%
“…Taking into account warts, it has been shown that in French women aged between 15 and 18 years, the incidence of genital warts significantly decreased in the period 2008-2012 after the introduction of the quadrivalent vaccine [8]; in Denmark, 5 years after the introduction of the same vaccine the incidence of genital warts decreased by 55% in women aged 12-35 years. Besides, in 12-29 years old men, the incidence of genital warts decreased by 37%, indicating the development of herd immunity [9].…”
Section: Hpv Epidemiology In Europe and In Italymentioning
confidence: 99%